(3GdWHbGJ GdcHjQs - (3eMeO Hf SYO Hf efjY GdRgQj, CHh YHO Gddg cGJH GdhGbOj, GHf SYO , J (B230 (3g` s
(3ChdgG (B:s
(3Ce SdeI hGSegG gfO HfJ CHj CejI s
(3BNQgG (B:s
(3MOKJfi QbjI HfJ YHO GdQMef Yf CegG MLI HfJ bQW , bGdJ (B: (3Cdbi GdebGe ef GdSeGA BNQ WHbGJ GdfSGA hgh BNQ GdcJGH s
(3GdeNWhW jJVef JQGLe GdfSGAs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B136 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B21s
Keywords: (3GdJGQjNs